La donación remuneratoria: una aproximación crítica a su naturaleza y a sus alcances - Bautista Quispe, Ulises (2024)
The remunerative donation has a treatment partially different from that of an ordinary donation; neither the rules of revocation nor those of the obligation of maintenance (including the rules that protect the ‘legítima’) do not apply to it. However, in the Civil Code such treatment is omitted and there is a tendency to equate it to an onerous act or a payment, which is not uncommon to find also in several sectors of the national and foreign doctrine.The author criticizes these positions, pointing out several deficiencies, and argues that the remunerative donation is a subtype of donation that is entered into freely. Furthermore, he argues that the remunerative donation should not be equated with mercantile interests, given its essence and the values it promotes. Likewise, in view of the legal gap in the Civil Code, the author identifies and specifies the scope that this contract should have.